2018
DOI: 10.1104/pp.18.00329
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis PIRL6 Is Essential for Male and Female Gametogenesis and Is Regulated by Alternative Splicing

Abstract: Plant intracellular Ras-group leucine-rich repeat (LRR) proteins (PIRLs) are related to Ras-interacting animal LRR proteins that participate in developmental cell signaling. Systematic knockout analysis has implicated some members of the Arabidopsis () family in pollen development. However, for, no bona fide knockout alleles have been recovered, suggesting that it may have an essential function in both male and female gametophytes. To test this hypothesis, we investigated expression and induced knockdown by RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 81 publications
(87 reference statements)
3
8
0
Order By: Relevance
“…Loraine et al revealed that AS participants in the reproduction development of Arabidopsis [62]. AS has been reported to regulate the formation of male and female gametogenesis in Arabidopsis [63], which also led to the male sterile in rice [23]. In this study, we have detected seven AS modes in the ovule of P. tabuliformis, there are more AS events in the FER than STE ovule (Fig.…”
Section: Discussionsupporting
confidence: 55%
“…Loraine et al revealed that AS participants in the reproduction development of Arabidopsis [62]. AS has been reported to regulate the formation of male and female gametogenesis in Arabidopsis [63], which also led to the male sterile in rice [23]. In this study, we have detected seven AS modes in the ovule of P. tabuliformis, there are more AS events in the FER than STE ovule (Fig.…”
Section: Discussionsupporting
confidence: 55%
“…In A. thaliana, a splice variant of auxin response factor 8 has been found to play a role in regulating endothecium lignification and stamen elongation (Ghelli et al, 2018). Plant intracellular Ras-group leucine-rich repeat protein 6 is necessary for female and male gametogenesis in A. thaliana, and it is regulated by AS (Forsthoefel et al, 2018). Moreover, many studies on AS have been performed in different plant species, such as A. thaliana, tomato, moso bamboo, and peanut (Wang et al, 2014;Wang et al, 2017;Ruan et al, 2018;Zhao et al, 2018;Clark et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in peanut (Arachis hypogaea), Arabidopsis thaliana, soybean (Glycine max), tomato (Solanum lycopersicum) and moso bamboo (Phyllostachys edulis), approximately 37%, 61%, 63%, 65%, and 49% of multi-exon genes undergo AS events, respectively (Marquez et al, 2012;Shen et al, 2014;Ruan et al, 2018;Zhao et al, 2018;Clark et al, 2019). Furthermore, researchers have found that AS also plays important roles in male and female gametogenesis, seed germination in A. thaliana, plant-pathogen interactions in wheat (Triticum aestivum), and mineral nutrient homeostasis maintenance in rice (Oryza sativa) (Dong et al, 2018;Forsthoefel et al, 2018;Tognacca et al, 2019;Zhang H. et al, 2019). These findings indicate that AS is essential for plant survival and reproduction.…”
Section: Introductionmentioning
confidence: 99%
“…GEM1 encodes a microtubule-associated protein and GEM3 is required for microtubule organisation and mitotic progression. Additional proteins that are essential for gametophyte development include ABORTED GAMETOPHYTE 1 (Cui et al, 2015), the DC1-domain protein VACUOLELESS GAMETOPHYTES (D’IppĂłlito et al, 2017), and the leucine-rich repeat protein PIRL6 (Forsthoefel et al, 2018). Whether AOG2 acts upstream or downstream of these other factors remains to be determined, but if any of them are translated in the ER, they are putative AOG2 targets.…”
Section: Resultsmentioning
confidence: 99%